Creating a measure of portion control self-efficacy. (January 2015) - Fast, Lindsey C.; Harman, Jennifer J.; Maertens, Julie A.; Burnette, Jeni L.; Dreith, Francesca
Abstract: Objective: Over the last few decades, food portion sizes have steadily increased by as much as 700% (Young & Nestle, 2002). Food portions are often much larger than dietary guidelines recommend, leaving individuals to manage their food consumption on their own and making it necessary to understand individual factors impacting food consumption. In the current paper, we focus on self-efficacy for portion control. Method: Specifically, across three studies, we developed and validated a new measure of portion control self-efficacy (PCSE). Result: The PCSE measure yielded good fit statistics and had acceptable test–retest reliability using two cross-sectional surveys (Studies 1(a) and 1(b)). Results from Study 2 demonstrated construct and predictive validity of the PCSE using the Food Amount Rating Scale (FARS; Dohm, & Striegel-Moore, 2002). Study 3 offered additional support for reliability and validity with a sample of overweight and obese adults currently trying to lose weight. Conclusions: Overall, findings indicate that the new PCSE measure is reliable and valid. Individuals often make inaccurate food portion estimates (Slawson & Eck, 1997; Yuhas, Bolland, & Bolland, 1989) which can lead to overeating and weight-gain. Thus, the discussion centers on the need to incorporate PCSE in future research and intervention work targeting weight loss, health, and food consumption. Graphical abstract: Highlights: We developed and tested a measure of portion control self-efficacy (PCSE). In Study 1(a), the measure of PCSE had overall good reliability and validity. Study 1(b) showed good fit for the across multiple time periods. Study 2 indicated that the PCSE scale has good predictive validity. Study 3 demonstrated test–re-test reliability in a sample of overweight adults.